An intelligent battery information management system to support information sharing and vehicle routing planning for battery distribution in Hong Kong. (9th February 2015) - Wong, David W.C.; Choy, K.L.; Lin, Canhong; Lam, H.Y.; Lee, C.K.H.; Chow, Harry K.H.; Pang, Grantham K.H.
Recently, the deployment of electric vehicles (EV) has been recognised as a key element for establishing sustainable transport systems within countries. Research studies have been conducted to tackle challenges regarding the commercial introduction of EV. However, the current plug–in EV infrastructure poses operational limitations, causing users refusing to change from fossil–fuelled vehicles to EV. To eliminate the limitations of long charging time and huge infrastructure costs of the current EV models, an intelligent battery information management system (IBIS) is designed for supporting battery switching logistics operations. The system shows the potential value of the battery switching management and the minimisation of the supply chain cost. A case study in launching the proposed model in Hong Kong is conducted. The result provides a practical solution to balance the level of battery charging efficiency in the battery management hub, service rate of battery switching stations, and the inventory cost of holding batteries.